Economics in the long run : New Deal theorists and their legacies, 1933-1993 - Rosenof, Theodore (Chapel Hill : University of North Carolina Press, 1997)
Though understandably preoccupied with the immediate problems of the Great Depression, the generation of economists that came to the forefront in the New Deal Era of the 1930s also looked ahead to the long-term consequences of the crisis and proposed various solutions to prevent its recurrence. Theodore Rosenof examines the long-run theories and legacies of four of the leading members of this generation: John Maynard Keynes of Great Britain, who influenced the New Deal from afar; Alvin Hansen and Gardiner Means, who fought over the direction of New Deal policy; and Joseph Schumpeter, an opponent of the New Deal.
pt. 1. The New Deal Era. 1. The Focus on Structure. 2. Keynesianism as Long-Run Economics. 3. Gardiner C. Means and the Corporate Revolution. 4. Alvin H. Hansen and Continental Theory. 5. Alvin H. Hansen and Secular Stagnation. 6. Hansen versus Means, Means versus Keynes. 7. Debates over Stagnation and Structure -- pt. 2. Boom Times to Troubled Times. 8. The Schumpeterian Alternative. 9. Eclipse in the Postwar Boom. 10. Persistence in the Postwar Boom. 11. The Refocus on Corporate Structure and Power. 12. Schumpeterian Revival and Long Waves. 13. The Specter of Secular Stagnation. 14. Public Policies for the Long Run.
Includes bibliographical references (pages 179-217) and index.
Print version record.
English.
JSTOR
Keywords: Keynes, John Maynard, -- 1883-1946.; Hansen, Alvin H. -- 1887-1975.; Means, Gardiner C. -- 1896-1988.; Schumpeter, Joseph A., -- 1883-1950.; Hansen, Alvin H. -- 1887-1975; Keynes, John Maynard, -- 1883-1946; Means, Gardiner C. -- 1896-1988; Schumpeter, Joseph A., -- 1883-1950; Economics -- History -- 20th century; United States -- Economic policy; New Deal, 1933-1939.; Économie politique -- Histoire -- 20e siècle.; États-Unis -- Politique économique.; New Deal; New Deal; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; HISTORY -- United States -- General; New Deal, 1933-1939; Economic policy; Economics; United States; Wirtschaftstheorie; New Deal; USA; Business & Economics; Economic Theory; Geschichte 1933-1993.; 1900-1999; History